Dimensionamento do semáforo do cruzamento das ruas Matriz da Conceição e Siqueira Campos em Tucuruí-PA à luz do novo manual de sinalização semafórica do Denatran - COSTA, Glenda da Silva (2018)
Each year, the fleet of vehicles is increasing in cities, causing impacts on traffic and people's quality of life. The function of Traffic Engineering is to minimize these impacts by promoting the comfortable, efficient and safe movement of people and vehicles in the road network. It is necessary, however, that this increase in the fleet be accompanied by traffic studies and investments in road infrastructure. Traffic Engineering is especially important in the municipality of Tucuruí, located in the State of Pará, Brazil, for although in a period of ten years the fleet has increased eight times more than the population, the timing of all traffic signals in the municipality were defined without following any technical recommendations. It is well known that improper installations or inadequate traffic signal timing hinders the traffic flow, promotes discrediting of traffic signs and, consequently, make traffic unsafe. Therefore, it was sought to analyze the traffic signals of the crossroad of the Matriz da Conceição and Siqueira Campos streets, for in this place there is a high disrespect to the traffic signals. This analysis was made by comparing the current traffic signal timing design with a new one, which was carried out following the recommendations of the Manual Brasileiro de Sinalização Semafórica Volume V – Sinalização Semafórica, a Brasilian manual of traffic signal. To carry out the new design, it was necessary to determine the saturation flow rate, one of the main parameters in the traffic signals timing design. This determination was made in two ways: by means of the signalized intersection methodology, and by means of the direct measurement of prevailing saturation flow rates methodology. The latter, especially due to consideration of motorcycles during recording observation, did not have sufficient data to achieve consistent and satisfactory results. Therefore, the traffic signal timing design in which the former methodology was used were compared to the current design. It was found that the current one is not adequate to the crossroad traffic conditions: all approaches have the same green time and the same red time, despite having different traffic flows. The new traffic signal timing presented adequated results to the traffic conditions of the crossroad: the cycle time, the green time of the approaches with lower flow (in which there is a large occurrence of zero flow rate during green time), and the red time from all three approaches, were decreased, which may prevent excessive waiting.